2012
DOI: 10.7314/apjcp.2012.13.8.4051
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate (Punica granatum) Peel Extract Efficacy as a Dietary Antioxidant against Azoxymethane-Induced Colon Cancer in Rat

Abstract: Functional foods include antioxidant nutrients which may protect against many human chronic diseases by combating reactive oxygen species (ROS) generation. The purpose of the present study was to investigate the protective effect of pomegranate peel extract (PPE) on azoxymethane (AOM)-induced colon tumors in rats as an in vivo experimental model. Forty Sprague-Dawley rats (4 weeks old) were randomly divided into 4 groups containing 10 rats per group, and were treated with either AOM, PPE, or PPE plus AOM or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 18 publications
8
26
0
Order By: Relevance
“…In first part, we observed that mean blood glutathione levels are significantly reduced in head and neck cancer compared with respective controls. Our results are in agreement with earlier studies which have demonstrated that glutathione levels differ in patients of head and neck malignancies and this depletion could be due to imbalance in free-radical and antioxidant homeostasis in body fluids during carcinogenesis (Singh et al, 2008;Waly et al, 2012;Shetty et al, 2013). The other plausible explanation for decreased levels of glutathione observed in head and neck cancer patients is possibly GSH, being exhausted as a main low molecular weight antioxidant in cellular protection (Komatsu et al, 2008;Trachootham et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…In first part, we observed that mean blood glutathione levels are significantly reduced in head and neck cancer compared with respective controls. Our results are in agreement with earlier studies which have demonstrated that glutathione levels differ in patients of head and neck malignancies and this depletion could be due to imbalance in free-radical and antioxidant homeostasis in body fluids during carcinogenesis (Singh et al, 2008;Waly et al, 2012;Shetty et al, 2013). The other plausible explanation for decreased levels of glutathione observed in head and neck cancer patients is possibly GSH, being exhausted as a main low molecular weight antioxidant in cellular protection (Komatsu et al, 2008;Trachootham et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…In our recent works, it was observed that mean blood glutathione levels are significantly reduced in head and neck cancer compared with respective controls [10]. Our results are in agreement with earlier studies which have demonstrated that glutathione levels differ in patients of head and neck cancers and this depletion could be due to imbalance in free-radical and antioxidant homeostasis in body fluids during carcinogenesis [10][11][12][13][14]. The other plausible explanation for decreased levels of glutathione observed in head and neck cancer patients is possibly GSH, being exhausted as a main low molecular weight antioxidant in cellular protection [15,16].…”
Section: Discussionsupporting
confidence: 83%
“…Finally, these can develop into polyps and eventually into CRC. Plant constituents and their derivatives may exert significant effects on decreasing the incidence of ACF in the colon (Waly et al, 2012;Tammasakchai et al, 2012;Ansil et al, 2013;Guizani et al, 2013;Madrigal-Bujaidar et al, 2013). Treating the animals with luteolin during the AOM-induced CRC animals showed reduced incidence of ACF (Ashokkumar and Sudhandiran, 2008).…”
Section: Luteolin Effects On Preneoplastic Lesionsmentioning
confidence: 99%